Has economic growth in Mozambique been pro-poor? - James, Robert C.; Arndt, Channing; Simler, Kenneth R. (International Food Policy Research Institute, 2005)
This discussion paper examines trends in inequality in Mozambique, which in 1996 was one of the world’s poorest countries. In fact, it was so poor that mean per capita consumption was actually below the absolute poverty line. Between 1996 and 2002, however, the economy grew by 62 percent cumulatively. Although the poverty headcount declined from 69 to 54 percent, more than half of the population continued to live below the poverty line. The question then is to what extent has economic growth benefited the poor? Is it pro-poor? Although the term “pro-poor” is pervasive in the literature today, there is no consensus on its definition. This paper considers the pattern of growth across the entire income distribution.